2014
DOI: 10.1039/c4ra00674g
|View full text |Cite
|
Sign up to set email alerts
|

Iodonium ylides for one-step, no-carrier-added radiofluorination of electron rich arenes, exemplified with 4-(([18F]fluorophenoxy)-phenylmethyl)piperidine NET and SERT ligands

Abstract: Iodonium ylide precursors of electron rich arenes, i.e. the NET and SERT ligands 4-((3- and 4-fluorophenoxy)phenylmethyl)piperidine, served as model compounds for the direct substitution with n.c.a. [18F]fluoride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 13 publications
0
46
0
1
Order By: Relevance
“…This technology was introduced by Satyamurthy and Barrio using barbituric or Meldrum’s acid auxiliaries (6). A recent study by Coenen and coworkers demonstrated the satisfactory application of this method using Meldrum’s acid auxiliaries, but led to non-regiospecific labeling and formation of several byproducts (7). Concurrently, we explored the application of iodonium ylide precursors with barbituric acid and Meldrum’s acid auxiliaries for 18 F-labeling but also found yields to be sub-optimal (8).…”
Section: Introductionmentioning
confidence: 99%
“…This technology was introduced by Satyamurthy and Barrio using barbituric or Meldrum’s acid auxiliaries (6). A recent study by Coenen and coworkers demonstrated the satisfactory application of this method using Meldrum’s acid auxiliaries, but led to non-regiospecific labeling and formation of several byproducts (7). Concurrently, we explored the application of iodonium ylide precursors with barbituric acid and Meldrum’s acid auxiliaries for 18 F-labeling but also found yields to be sub-optimal (8).…”
Section: Introductionmentioning
confidence: 99%
“…Parenthetically, novel methods reported for 18 F-labeling of substrates that are not activated for S N Ar substitutions can be adapted for [ 18 F]FIBG synthesis and efforts are under way in this direction in our laboratory. These methods include use of diaryl iodonium salts [21, 22] and iodonium ylide [23] precursors, and those mediated by nickel, palladium, and copper [2427]. …”
Section: Introductionmentioning
confidence: 99%
“…5 The first example was reported by Coenen and colleagues, who used iodonium ylide precursors 2 derived from Meldrum’s acid (building on promising initial work patented by Satyamurthy and Barrio 5a ) to synthesize fluorophenoxyethers 3 , which are potential radioligands for PET imaging of the serotonin and norepinephrine (reuptake) transporters (Scheme 1b). 5b The concept was expanded by Vasdev, Liang and coworkers who introduced spirocyclic iodonium ylides 4 to address precursor stability issues of the earlier ylides. 5c The spirocyclic iodonium ylides are stable crystalline materials that are reactive towards fluorine-18.…”
Section: Aromatic Fluorination With Fluorine-18mentioning
confidence: 99%
“…5b The concept was expanded by Vasdev, Liang and coworkers who introduced spirocyclic iodonium ylides 4 to address precursor stability issues of the earlier ylides. 5c The spirocyclic iodonium ylides are stable crystalline materials that are reactive towards fluorine-18. They have been used to synthesize [ 18 F]fluoro(hetero)arenes bearing electron donating or electron withdrawing groups in moderate to good radiochemical yields.…”
Section: Aromatic Fluorination With Fluorine-18mentioning
confidence: 99%